Time Management for Result Oriented Learning - Chioma, Festus; Ekpete, Ozioma Adanwo (Mediterranean Journal of Social Sciences, 2011)
At the heart of every institution (mostly learning institution) is repertoire of essential skills which every serious individualstrives to know. No one is perfect but becomes more proficient as he continues to work and practice. In fact effective individualare never satisfied, they are curiously in search of attitudes to sharpen their results. Time management is essential for achievingpositive results in( learning) institutions, however it has not been adequately enhanced by individual. This paper examines howtime can be managed, its benefits and need for private time table (PTT).